ENGLISH LANGUAGE USAGE IN THE WORKPLACE: CHALLENGES AND STRATEGIES FOR IMPROVEMENT - Purwandari, Junita Duwi; Kamila, Fatima; Pelawi, Rinawati (Conscientia - Journal on Language, Literature, and Culture, 2025)
In today’s globalized business environment, English plays a vital role in professional communication, especially in non-English-speaking countries like Indonesia. This study explores English language usage in Indonesian workplaces, the challenges employees encounter, and their motivation to improve proficiency. It aims to understand how English affects workplace dynamics and identify strategies to enhance communication. Using a quantitative, cross-sectional survey design, data were collected through a structured questionnaire completed by employees across various sectors. The 26-item instrument measured language use, perceived difficulties, attitudes, and motivation on a 5-point Likert scale. Descriptive statistical analysis was used to interpret the findings. Results indicate that receptive skills (e.g., reading English documents) are used more frequently than productive skills (e.g., speaking in meetings). Participants reported moderate difficulties in expressing ideas and understanding accents, but showed strong awareness of English’s importance and high motivation to improve. Additionally, there was a strong expectation for organizational support, such as training programs and communication policies. This study highlights the need for targeted interventions to bridge communication gaps and promote effective English usage. With high employee motivation and clear institutional demand, organizations have a valuable opportunity to strengthen their workforce's communicative competence and global competitiveness.